Exploring Multidimensional Relationships between Educational Situation Perception, Teacher Support, Digital Learning Engagement, and Academic Self-Efficacy in Elementary School - Dita Amelia Putri; Muhammad Alie Muzakki (GENFABET: Generasi Pendidikan Dasar, 2026)
This study examines the structural relationships among students’ perceptions of the learning environment, perceived teacher support, academic self-efficacy, and students’ engagement in digital learning in elementary school digital learning contexts. A quantitative survey approach was employed, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that academic self-efficacy significantly predicts students’ participation in digital learning activities. Teacher support significantly contributes to strengthening academic self-efficacy and indirectly influences digital learning engagement through the improvement of students’ academic confidence. In contrast, educational situation perception does not show a significant direct relationship with either academic self-efficacy or digital learning engagement. The sequential mediation pathway involving teacher support and academic self-efficacy is statistically confirmed. The model demonstrates satisfactory explanatory power and predictive relevance. The results suggest that psychologically driven factors supported by effective pedagogical practices play a more central role in fostering students’ digital engagement than contextual perceptions operating independently. These findings highlight the mediating role of academic self-efficacy within the multidimensional framework tested in this study.